2000
DOI: 10.1097/00000478-200005000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Crohn's Colitis-Like Changes in Sigmoid Diverticulitis Specimens Is Usually an Idiosyncratic Inflammatory Response to the Diverticulosis Rather Than Crohn's Colitis

Abstract: The clinical outcome and optimum classification of patients who have sigmoid resection specimens that show the histologic features of Crohn's disease (CD) and diverticulitis is not well defined. Historically, these patients were considered to have coexistent diseases, but recent studies have suggested that the CD-like changes are part of the inflammatory reaction of the diverticulitis. Sorting out these issues has been complicated by the lack of distinction between patients with and without CD in other regions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
76
0
4

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(83 citation statements)
references
References 62 publications
3
76
0
4
Order By: Relevance
“…In Crohn's disease, as well, studies have shown that over 80% of adults are usually diagnosed well before age 40 [6][7][8] . Like other forms of idiopathic inflammatory bowel diseases, the cause and pathogenesis needs to be better characterized and elucidated [1,5,9] . Endoscopic examination reveals a localized sigmoid inflammatory process with normal rectal and proximal colonic mucosa.…”
Section: Clinical Features Of Scadmentioning
confidence: 99%
See 1 more Smart Citation
“…In Crohn's disease, as well, studies have shown that over 80% of adults are usually diagnosed well before age 40 [6][7][8] . Like other forms of idiopathic inflammatory bowel diseases, the cause and pathogenesis needs to be better characterized and elucidated [1,5,9] . Endoscopic examination reveals a localized sigmoid inflammatory process with normal rectal and proximal colonic mucosa.…”
Section: Clinical Features Of Scadmentioning
confidence: 99%
“…In recent years, other less common, but distinct types of inflammatory disease have become better recognized. One segmental form associated with diverticulosis, usually involving only the sigmoid colon, is the so-called "SCAD syndrome", or more precisely, segmental colitis associated with diverticulosis (SCAD) [1][2][3][4][5] .…”
Section: Introductionmentioning
confidence: 99%
“…In one study of 29 patients with CDlike diverticulitis, only two developed CD, and both of these occurred in other regions of the bowel. 89 As mentioned above, many types of drugs may cause chronic or chronic active colitis that mimics IBD, in both biopsy and resection specimens. Ipilimumab, a drug used for the treatment of metastatic melanoma, has been reported to show UC-like inflammatory changes in the colon.…”
Section: Crohn's Disease With Uc-like Featuresmentioning
confidence: 99%
“…[86][87][88] Rarely, acute diverticulitis may mimic CD in resection specimens. 89,90 This phenomenon may be recognized by the fact that CD-like changes are isolated to the segment of colon involved with diverticular disease. In one study of 29 patients with CDlike diverticulitis, only two developed CD, and both of these occurred in other regions of the bowel.…”
Section: Crohn's Disease With Uc-like Featuresmentioning
confidence: 99%
“…Studies suggest that Crohn-like changes within the sigmoid that harbors diverticular disease are an idiosyncratic inflammatory response to the diverticulosis rather than coexistent CD in the overwhelming majority of patients who do not have a prior diagnosis of inflammatory bowel disease. 59 Pathologists should be cautious about making the diagnosis of sigmoid Crohn colitis in the context of diverticulitis unless there is CD in other parts of the bowel.…”
Section: Diverticular Disease-associated Colitis Clinical Featuresmentioning
confidence: 99%